Essays on corporate risk : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, Albany, New Zealand - Wen, Yantao (Massey University, 2024)
There is widespread recognition that corporate risk can substantially affect firms’ operations. However, one challenging problem, which still requires investigation, is how firms assess their risk profiles. The main objective of this thesis is to systematically assess corporate risk profiles, with comprehensive attention to the effectiveness of risk management schemes, the identification of the firm characteristic-based internalised transmission mechanism of macroeconomic uncertainty, and the evaluation of the internalized macroeconomic uncertainty from the perspective of corporate investment. Motivated by exploring the role of corporate risks in firms’ operations, this thesis carries out three independent but related studies focusing on the Chinese market to contribute to this strand of literature by discussing the effectiveness of risk hedging strategy by financial derivatives, exploring the transmission mechanism of uncertainty exposure, and investigating the investment efficiency of firms with different exposures under different periods of uncertainty. The first empirical study investigates the factors influencing firms' hedging decisions and the impact of hedging on firm performance. The results indicates that larger firms with more operational cash flow, less tax shielding, higher R&D investment level, and higher possibility of bankruptcy are more likely to use financial derivatives to hedge firm risks, while the firms’ ownership structure does not play a significant role in the process. The study also documents that, in general, using derivatives negatively affects the firms’ performance in the Chinese market, and such effect shows no difference between the state-owned and non-state-owned firms. After separating the outperforming firms with the underperforming firms, the study further finds that the negative effect of derivatives on firm performance only exists among underperforming firms. This suggests that while poorly performing firms are more likely to invest in financial derivatives, such a decision typically exacerbates rather than alleviates poor performance. The second study examines the role of corporate natures under economic policy uncertainty. Through introducing Bali, Brown, and Tang (2017)’s firm-level economic policy uncertainty exposures (EPU exposure), this study finds that EPU exposure is positively related to the proportion of state ownership. Moreover, debt financing serves as the channel through which state ownership exposes firms to economic policy uncertainty (EPU). Specifically, a higher percentage of state ownership results in higher leverage which, in turn, increases EPU exposure. After exploring the firms’ EPU exposure as well as the underlying mechanism, the third essay presents investment strategy from the perspectives of risk and corporate investment efficiency to empirically contribute to the epistemology on the controversy between risk and return. This essay finds EPU and a firm’s EPU exposure have inhibitory effects on a firm’s investment efficiency, with the effect of EPU exposure being exacerbated in a volatile market year. When the sample is split into four groups by EPU exposure and EPU, investment efficiency in higher EPU exposed firms presents a significant bifurcation, with the highest investment efficiency in lower EPU times and the lowest in higher EPU times, whereas there is no significant difference in lower EPU exposed firms. Consistent with the perspective of Fletcher (2000), this essay suggests investing in higher EPU exposed firms in tranquil market years and in lower EPU exposed firms in turbulent times.
Keywords: 350208 Investment and risk management